Novel pH sensor based on fiber optic coated bromophenol blue and cresol red - Fredy Kurniawan; Baginda Zulkarnain; Mohammad Teguh Hermanto; Hendro Juwono; Muhammad Rivai (Universitas Ahmad Dahlan, 2019)
Fabrication of pH sensor based on fiber optic coated bromophenol blue and cresol red has been done. Briefly, jacket in the middle part of the fiber optic was removed for 5 cm. Then the core of each of fiber optics was washed in ethanol. Nitric acid, demineralized water, and ethanol again consecutively. Then the cleaned core was coated using active material using sol-gel immobilization technique. Tetraehyl orthosilicate was used as a binder in the immobilization of active materials. Bromophenol blue will start change the color to yellow at below pH 3.00±0.01 and blue at above pH 4.60±0.01, while the cresol red will start change the color to yellow at below pH 7.20±0.01 and violet at above pH 8.80±0.01. The pH sensors which have been made show the sigmoidal response over pH from 1.00±0.01 to 11.00±0.01. The sensor has a better performance in comparation with the other sensor.